Negosiasi Sebagai Alternatif Penyelesaian Sengketa Perkara Konsumen: Studi Kasus Terhadap Korban Online Shop - Eli Triana; Fatimatuz Zehroh; Imroatul Azizah (Universitas Sains dan Teknologi Komputer, 2025)
Negotiation is the most common way of resolving disputes, including in everyday life, such as bargaining over prices in the buying and selling process. In essence, negotiation is a communication process between two or more parties who have different interests, and aims to reach a mutual agreement. Negotiation can not only be done in real life (meeting) but, negotiation can also be done online, especially in online buying and selling. Online buying and selling is a technological breakthrough that helps people to buy goods without coming to a place/store. So that it can make it easier for consumers to buy goods/services. This study aims to examine the extent to which negotiation can resolve consumer cases online. The method used is descriptive qualitative with primary data obtained from interviews while secondary data is obtained by reviewing books and journals. The approach used is a case study approach. The results of the study show that negotiation is quite effective in resolving online-based consumer cases although not 100% because there are several obstacles that hinder the negotiation process, namely slow response/non-response of business actors, difficult return process. So that to achieve fast negotiation requires activeness and good faith from each party.